Fast diploidization in close mesopolyploid relatives of Arabidopsis - Mandáková, Terezie; Joly, Simon; Krzywinski, Martin; Mummenhoff, Klaus; Lysak, Martin A (The Plant cell, 2010)
Mesopolyploid whole-genome duplication (WGD) was revealed in the ancestry of Australian Brassicaceae species with diploid-like chromosome numbers (n = 4 to 6). Multicolor comparative chromosome painting was used to reconstruct complete cytogenetic maps of the cryptic ancient polyploids. Cytogenetic analysis showed that the karyotype of the Australian Camelineae species descended from the eight ancestral chromosomes (n = 8) through allopolyploid WGD followed by the extensive reduction of chromosome number. Nuclear and maternal gene phylogenies corroborated the hybrid origin of the mesotetraploid ancestor and suggest that the hybridization event occurred approximately 6 to 9 million years ago. The four, five, and six fusion chromosome pairs of the analyzed close relatives of Arabidopsis thaliana represent complex mosaics of duplicated ancestral genomic blocks reshuffled by numerous chromosome rearrangements. Unequal reciprocal translocations with or without preceeding pericentric inversions and purported end-to-end chromosome fusions accompanied by inactivation and/or loss of centromeres are hypothesized to be the main pathways for the observed chromosome number reduction. Our results underline the significance of multiple rounds of WGD in the angiosperm genome evolution and demonstrate that chromosome number per se is not a reliable indicator of ploidy level.
Keywords: molekulární sekvence - údaje; karyotypizace; Arabidopsis; Diploidy; chromozomy rostlin; Phylogeny; Chromosomes, Plant; fylogeneze; Karyotyping; diploidie; Molecular Sequence Data